Response of the ocean mixed layer, off the east coast of peninsular Malaysia, during the north-east and southwest Monsoons - Nasir Saadon, M. (1997)
The behavior of the mixed layer, off Kuala Terengganu, during the north-east and south-west monsoons is addressed. Temperature and salinity profiles, for both seasons, are analyzed. The results are quite conclusive. In the mixed layer, temperature and salinity have different characteristics during each season, being lower during the north-east monsoon. The depth of the mixed layer is shallower during the south-west monsoon. Two distinctive water masses are detected during both seasons.